Internal differentiation within multinational corporations - Ghoshal, Sumantra; Nohria, Nitin (Strategic Management Journal, 1989)
Abstract This paper argues that the internal structure in complex, multi‐unit organizations such as a multinational corporation (MNC) is not homogeneous throughout the organization, but is systematically differentiated so as to ‘fit’ the different environmental and resource contingencies faced by the different national subsidiaries. Based on a survey of 66 of the largest European and North American MNCs, yielding data on 618 cases of headquarters‐subsidiary relations, it is shown that the different contextual conditions faced by the different subsidiaries of the MNC can be meaningfully classified into four generic situations. Furthermore, for each of these situations the exchange relation between the MNC headquarters and the subsidiary is characterized by a ‘fit’ governance structure consisting of a different combination of structural elements such as centralization of authority, formalization of rules and systems, and normative integration of members. Following the existing literature, these ‘fit’ structures are labeled in this paper as hierarchical, federative, clan and integrative. The multinational is then described as an internally differentiated organization in which each headquarters‐subsidiary link corresponds to one or the other of these administrative forms.